2005
DOI: 10.1152/ajprenal.00097.2005
|View full text |Cite
|
Sign up to set email alerts
|

PPARγ agonists exert antifibrotic effects in renal tubular cells exposed to high glucose

Abstract: Collagen IV was not induced by high D-glucose. L-805645 and pioglitazone suppressed collagen IV to 68.0 Ϯ 14.5 (P Ͻ 0.05) and 46.5 Ϯ 11.6% (P Ͻ 0.01) vs. high D-glucose, respectively. High D-glucose increased the nuclear binding of NF-B to 167 Ϯ 22.4% (P Ͻ 0.05), which was not modified with PPAR␥ agonists. In conclusion, PPAR␥ agonists exert antifibrotic effects in human PTC in high glucose by attenuating the increase in AP-1, TGF-␤1, and the downstream production of the extracellular matrix protein fibronecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
59
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 37 publications
9
59
0
3
Order By: Relevance
“…Mezzano et al [30] reported that the activation of NF-κB and chemokines such as CCL2 and RANTES (regulated upon activation, normal T expressed and secreted) was strongly upregulated in renal tissues of human diabetic nephropathy. Moreover, high glucose upregulates peroxisome proliferator-activated receptor-γ (PPAR-γ), and PPAR-γ agonists exert antifibrotic, anti-proliferative and anti-inflammatory effects in renal proximal tubular cells under high glucose conditions by attenuating the increase in activator protein-1, TGFB1 and the downstream production of the extracellular matrix protein [31,32]. These data also suggest that inflammatory mechanisms are involved in the progression of diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 96%
“…Mezzano et al [30] reported that the activation of NF-κB and chemokines such as CCL2 and RANTES (regulated upon activation, normal T expressed and secreted) was strongly upregulated in renal tissues of human diabetic nephropathy. Moreover, high glucose upregulates peroxisome proliferator-activated receptor-γ (PPAR-γ), and PPAR-γ agonists exert antifibrotic, anti-proliferative and anti-inflammatory effects in renal proximal tubular cells under high glucose conditions by attenuating the increase in activator protein-1, TGFB1 and the downstream production of the extracellular matrix protein [31,32]. These data also suggest that inflammatory mechanisms are involved in the progression of diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 96%
“…The thiazolidinedione compounds and certain prostaglan- dins have been used to demonstrate that activation of PPAR␥ inhibits collagen synthesis (18) and fibrosis in lung (14,15,19,57), kidney (8,9,58), liver (10,11,33,36,59), cardiac fibroblasts (60), and skin (61). The issue of endogenous ligand for PPAR␥ in cells has been controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Synthetic antagonists of PPAR␥ are also available to inhibit PPAR␥ activity (5-7). Activation of PPAR␥ by agonists attenuates fibrosis in several organs, including kidneys (8,9), liver (10,11), heart (13), and lungs (14,15), and arteries in atherosclerosis (12) . Several studies suggest that PPAR␥ inhibits extracellular matrix synthesis, including collagen (16 -18).…”
mentioning
confidence: 99%
“…Administration of rosiglitazone (5 mg/kg for 20 d) to pregnant diabetic rats leads to inhibition of mesangial cell proliferation, downregulation of apoptosis, and reduced responsiveness to angiotensin II (1). Pioglitazone, another peroxisome proliferator-activated receptor-␥ agonist, exerts antifibrotic effects at 10 M in renal tubular cells exposed to high glucose (2) and reduces extracellular matrix production at 1 to 3 M after incubation with LDL (3). In puromycin aminonucleoside nephropathy, there is a decrease in podocyte injury, glomerulosclerosis, infiltrating glomerular macrophages, and plasminogen activator inhibitor-1 mRNA expression after treatment with pioglitazone, 10 mg/kg/d for 6 to 12 wk (4).…”
mentioning
confidence: 99%